Calcium, Vitamin D and Health (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Calcium is the main mineral in the body, involved in a variety of structural and functional roles. The maintenance of calcium homeostasis is perhaps the most studied function of vitamin D. This Special Issue of Nutrients, “Calcium, Vitamin D and Health” contains 12 original publications and two reviews investigating the contribution of (mainly) vitamin D and calcium on relevant health outcomes in a variety of populations, which reflect the evolving and broad interest of researchers on this topic.